Meta-Analysis: Incision and Curettage Superior to Steroid Injection for Chalazion Treatment - Aurilia Afia Bharata; Made Chindy Dwiyanti Marheni Putri; Delfitri Lutfi (Vision Science and Eye Health Journal, 2026)
Introduction: The most common inflammatory lesion of the eyelid, chalazion, can be treated in several ways. The optimal course of treatment is difficult to determine due to the high likelihood of recurrence. Purpose: This study aims to evaluate the outcomes and recurrence rates of chalazion treated with incision and curettage (I&C) compared with steroid injections. Methods: Publications were retrieved from PubMed, ScienceDirect, and Google Scholar. Data on successful intervention, recurrences, and time to resolution were analyzed using RevMan 5.4. Results: Twelve studies published between 2018 and 2022 were included in this review, comprising 1,122 participants. The subjects were patients with primary chalazion, some of whom had failed conservative treatment. Chalazion size is variable; in some studies, it is grouped into small, medium, and large. We found that 577 participants received I&C, with a success rate of 82.15%, and 545 received steroid injections, with a success rate of 73.58%. Our meta-analysis showed an odds ratio of 0.59 (p = 0.0004). After the first procedure, recurrence rates were reported in 3 of the 12 studies, ranging from 3.3% to 8% for I&C and from 10% to 34% for steroid injection (SI). Conclusions: This study found a significant difference between the two interventions, favoring I&C, although most included studies reported no significant differences. Treatment selection should therefore consider patient and clinician preferences, individual clinical factors, patient comfort and cooperation, potential side effects, and chalazion size, with steroid injection being more convenient and I&C showing a higher success rate.